Education and information needs for physicians about rare diseases in Spain - Ramalle-Gómara, Enrique (Orphanet J Rare Dis, 2020)
BACKGROUND: Rare diseases are a priority objective for public health systems. Given its complexity, late and misdiagnoses occur very often which causes mental and physical burden for patients and family. This would be caused, in part, for unprepared clinicians in this field. The aim of this study was to report the training needs and the perceived shortcomings of Spanish physicians of the public health system in the diagnosis, treatment and monitoring of patients with rare diseases. METHODS: We used a descriptive cross-sectional study through an “ad hoc” survey of 26 questions was completed by 132 primary care physicians and 37 specialists during April and May 2018. RESULTS: Less than a third of the physicians had received training in rare disease during their undergraduate or postgraduate years, and for hospital professionals, they received more training in the postgraduate period. CONCLUSION: Primary care physicians and specialists showed low training level in rare diseases. An academical and continuous program on rare disease, as well as, multidisciplinary units and high quality practice guidelines are necessary to help to prevention and support clinical decisions and improve quality of care of patients and families.